Evaluasi Pelaksanaan Supervisi Keperawatan di Rumah Sakit Umum Daerah Panembahan Senopati Bantul - Dini Desi Harmatiwi; Sri Sumaryani; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
The purpose of this study is to evaluate the implementation of the supervision of nursing in Panembahan Senopati Bantul Hospital. This study is a descriptive qualitative research. All data derived from interviews, observation, and search documents. Sample of respondents is representative of the nursing supervisor scheduled in October 2015. The research variables: the implementation of nursing supervision, seen from the description of the implementation, engineering, area, barriers of implementation, supervision and evaluation program monitor. Of the 67 times the supervision scheduled in October 2015 only 17 were implemented (25.4%). Figures noncompliance supervisor in the execution of supervision is still quite high. The majority of supervisors do with indirect supervision. Supervision has not been carried out throughout the area should be. Barriers to implementation of supervision include external and internal obstacles. Program monitoring and evaluation of supervision is still not implemented. Supervision of nursing has not gone up, judging from the absence rate of non-compliance supervisor and implementation is quite high, and there are still incomprehension supervisor of engineering and supervisory area should be.